2016
DOI: 10.1016/j.kint.2016.02.032
|View full text |Cite
|
Sign up to set email alerts
|

APOL1 renal-risk genotypes associate with longer hemodialysis survival in prevalent nondiabetic African American patients with end-stage renal disease

Abstract: Relative to European Americans, evidence supports that African Americans with end-stage renal disease (ESRD) survive longer on dialysis. Renal-risk variants in the apolipoprotein L1 gene (APOL1), associated with non-diabetic nephropathy and less subclinical atherosclerosis, may contribute to dialysis outcomes. Here, APOL1 renal-risk variants were assessed for association with dialytic survival in 450 diabetic and 275 non-diabetic African American hemodialysis patients from Wake Forest and Emory School of Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 37 publications
5
32
1
Order By: Relevance
“…These results extend the work of Ma et al [15] who made a similar observation, namely that APOL1 high risk genotypes are associated with longer hemodialysis survival in nondiabetic subjects ( n = 275, HR 0.57) but not in diabetic subjects ( n = 450, HR 1.29). In our study, which lacks APOL1 genotype data but has larger sample sizes, the AA survival advantage was observed in the APOL1 -associated nephropathy group including ESRD attributed to DM, hypertension, and APOL1-enriched GN.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results extend the work of Ma et al [15] who made a similar observation, namely that APOL1 high risk genotypes are associated with longer hemodialysis survival in nondiabetic subjects ( n = 275, HR 0.57) but not in diabetic subjects ( n = 450, HR 1.29). In our study, which lacks APOL1 genotype data but has larger sample sizes, the AA survival advantage was observed in the APOL1 -associated nephropathy group including ESRD attributed to DM, hypertension, and APOL1-enriched GN.…”
Section: Discussionsupporting
confidence: 90%
“…APOL1 risk variants have been associated with progression to ESRD regardless of diabetes status [19]. However, Ma et al [15]found that APOL1 risk variants have been associated with longer hemodialysis survival only in nondiabetic AA patients. Hypertension-attributed ESRD (histologically likely to be arterionephrosclerosis) in AA is associated with APOL1 variants (OR 4.6 [20]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors estimated APOL1 genotype frequencies based upon reported causes of ESKD and these may be inaccurate [2]. Results confirmed those from a prior report where African Americans with APOL1 high-risk genotypes (G1G1, G2G2 and G1G2) had lower mortality than African Americans with low-risk genotypes and European Americans, a work that included APOL1 genotyping in a smaller cohort [3]. …”
supporting
confidence: 59%
“…20, 21 Some studies have found a higher risk of atherosclerotic disease in individuals with APOL1 high-risk genotype, although this finding has not been consistent across all studies. 21-23 Since cardiovascular disease is the leading cause of mortality in patients with CKD, it is plausible that APOL1 status may associate with a differential risk of death. For example, one recent study demonstrated a 30% excess mortality risk in older blacks with the high- versus low-risk APOL1 genotype.…”
Section: Introductionmentioning
confidence: 99%